CHD3 helicase domain mutations cause a neurodevelopmental syndrome with macrocephaly and impaired speech and language. Issue 1 (December 2018) - Snijders Blok, Lot; Rousseau, Justine; Twist, Joanna; Ehresmann, Sophie; Takaku, Motoki; Venselaar, Hanka; Rodan, Lance; Nowak, Catherine; Douglas, Jessica; Swoboda, Kathryn; Steeves, Marcie; Sahai, Inderneel; et al.
Abstract Chromatin remodeling is of crucial importance during brain development. Pathogenic alterations of several chromatin remodeling ATPases have been implicated in neurodevelopmental disorders. We describe an index case with a de novo missense mutation inCHD3, identified during whole genome sequencing of a cohort of children with rare speech disorders. To gain a comprehensive view of features associated with disruption of this gene, we use a genotype-driven approach, collecting and characterizing 35 individuals with de novoCHD3 mutations and overlapping phenotypes. Most mutations cluster within the ATPase/helicase domain of the encoded protein. Modeling their impact on the three-dimensional structure demonstrates disturbance of critical binding and interaction motifs. Experimental assays with six of the identified mutations show that a subset directly affects ATPase activity, and all but one yield alterations in chromatin remodeling. We implicate de novoCHD3 mutations in a syndrome characterized by intellectual disability, macrocephaly, and impaired speech and language. Chromodomain Helicase DNA-binding (CHD) proteins have been implicated in neurodevelopmental processes. Here, the authors identify missense variants inCHD3 that disturb its chromatin remodeling activities and cause a neurodevelopmental disorder with macrocephaly and speech and language impairment.